A template method to measure the t(t)over-bar polarisation - Aguilar-Saavedra, J. A. (2022)
We develop a template method for the measurement of the polarisation of t (t) over bar pairs produced in hadron collisions. The method would allow to extract the individual fractions of t(L)(t) over bar (L), t(R)(t) over bar (R), t(L)(t) over bar (R) and t(R)(t) over bar (L) pairs with a fit to data, where L, R refer to the polarisation along any axis. These polarisation fractions have not been independently measured at present. Secondarily, the method also provides the net polarisation of t and (t) over bar, as well as their spin correlation for arbitrary axes.